The effect of solid acid catalysts for biodiesel production - Samsudin, Rubyatul Adawiyah (2011)
In the present work, the performance of zirconia oxide (ZrO2), sulfated zirconia (SZ), sulfated zirconia-alumina (SZA), tungstated zirconia (WZ), tungstated zirconia-alumina (WZA), sulfated tin oxide (STO) and zeolite ZSM-5 for the transesterification of triacetin was investigated to study the effect of acidity on the conversion. The catalysts were characterized for their structure and acidity. The conversion of triacetin in the presence of solid acid catalyst using batch reactor was investigated. It was found that SZ gave highest triacetin conversion (61.5 %) among other solid catalysts studied. Acidity of the SZ was further modified with different molar (0.5 - 5.0 M) of sulfuric acid (H2SO4) and its performance for transesterification was tested. The results showed that SZ impregnated with 2.0 M of H2SO4 gave the highest triacetin conversion (68.5 %) due to its highest acidity of the catalyst and no reaction was observed for 4.0 M and 5.0 M of H2SO4. X-ray diffraction (XRD) characterization showed that tetragonal phase (2? = 30.2o) is a dominant structure of zirconia and the addition of sulfate ion up to 2.0 M did not considerably change the crystallinity of the catalyst. However, further additions of the sulfate ion would collapse the structure of zirconia. Infrared pyridine (IRpyridine) showed that no Bronsted and Lewis acid sites were present for 4.0 M and 5.0 M of H2SO4 due to the corrupted of zirconia structure. Scanning electron microscope (SEM) results found that the low concentration of sulphuric acid showed highly dense characteristic. Finally, the optimization of triacetin conversion was carried out using response surface methodology (RSM) in order to get the optimum biodiesel production for different parameters. As a result, 19:1 molar ratio of alcohol to triacetin, 191 min reaction time and 141 °C temperature gave the optimum condition for biodiesel production at 82.4 % conversion